A Haptic Interface to Enhance Sensory Processing in Children with ASD - Zamudio, Luis M.; González, Christian; Favela, Jesus; Tentori, Monica (Proceedings of the ACM International Conference on Interactive Media Experiences Workshops (IMXw); 2025: Proceedings of the ACM International Conference on Interactive Media Experiences Workshops, 2025)
Children with Autism Spectrum Disorder (ASD) often experience atypical sensory processing, affecting their engagement in daily activities. Traditional tactile therapies rely on subjective observations, while recent advances in haptic technology offer more quantitative interventions. This study introduces a haptic interface for digital tactile therapy, a digital application developed with a customized crayon base vibrotactile stylus pen to simulate various textures through a coloring activity. We conducted a formative prototype test with six sensory therapists and explored engagement with eight preschool children with ASD to observe a traditional tactile therapy dynamic and how the children use our prototype, revealing that all participants engaged with the haptic interface for an average of more than five minutes, some requesting additional use. Therapists found the tool to be novel and valuable, suggesting new digital exercise to integrate into sensory therapy. Future work will refine the app with exercises recommended by the therapist and explore long-term engagement, highlighting the importance of developing digital therapeutic tools for more engaging and effective sensory interventions.